Gold–glutathione complex catalysts with carbon support for non-mercury catalytic acetylene hydrochlorination. Issue 107 (3rd November 2016) - Qi, Xueyan; Li, Wei; Gu, Junjie; Guo, Cuili; Zhang, Jinli
Abstract : Adjusting the pH of the catalysts to a suitable value can make Au active species more dispersed on the catalysts, which improve the performance of the catalysts. Abstract : Gold–glutathione complex catalysts for acetylene hydrochlorination were prepared at different pH values. Coal-based columnar carbon, HAuCl4 ·4H2 O and glutathione (GSH) were added as the carrier, the precursor and the protective/reductive agent, respectively. The catalysts were characterized by Fourier transform infrared spectroscopy, ultraviolet spectrum, N2 adsorption/desorption, thermogravimetric analysis, temperature-programmed reduction/desorption, powder X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy. The highest activity is obtained over the Au1–GSH3/AC (pH 8.3) catalyst with the acetylene conversion of 82%, under the conditions of 170 °C and the C2 H2 gas hourly space velocity (GHSV) of 360 h −1 . It is indicated that the addition of GSH can result in the reduction of Au 3+ to Au + during the catalysts preparation process, the species of Au + and Au 0 coexist in the fresh Au1–GSH3/AC catalysts, with the individual content close to 50%. Compared with fresh Au/AC catalyst comprised of Au 3+ and Au 0, it is illustrated that the presence of Au + plays an important role in enhancing the catalytic activity. Adjusting the pH of the catalyst to a suitable value can make more active species disperse well on the catalysts, inhibit coke deposition and enhance the adsorption ability of reactants.